Budidaya Jagung Untuk Meningkatkan Hasil: Maize Cultivation to Increase Yield - safira, Adila putri; Rozaki, Zuhud; Wulandari, Retno; Distrianada, Ridho Ikbar (Universitas Muhammadiyah Yogyakarta, 2024)
Research conducted in Pandes, Wedi Subdistrict, Klaten District, Central Java Province aimed to determine the effect of the number of seeds and pruning on corn yield. The research used a 2 x 4 factorial complete randomized design with two factors, namely the number of corn seeds per planting hole and pruning. The results showed that all treatment parameters did not experience interaction except corn seed weight per cob. The largest seed weight was found in the combination of B1P2 (183.93 grams per cob) while the smallest was found in B1P0 (176.88 grams per cob).